If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 = 6x + -12 Reorder the terms: 7 + 3x = 6x + -12 Reorder the terms: 7 + 3x = -12 + 6x Solving 7 + 3x = -12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 7 + 3x + -6x = -12 + 6x + -6x Combine like terms: 3x + -6x = -3x 7 + -3x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 7 + -3x = -12 + 0 7 + -3x = -12 Add '-7' to each side of the equation. 7 + -7 + -3x = -12 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = -12 + -7 -3x = -12 + -7 Combine like terms: -12 + -7 = -19 -3x = -19 Divide each side by '-3'. x = 6.333333333 Simplifying x = 6.333333333
| -5x(x+2y-7)= | | 7x^2y+4xy^2-6xy+y= | | 10b-3b= | | X^3+x^2-6x-6=0 | | 8b+9m=21.40 | | 3x(x+3)=(x+3)(x+3) | | X-15+3(X+1)=5(X-2)+11 | | 5a-12=4a | | -4000-40-(-4)= | | -3X+5-4(X-1)=-2(X+1)-24 | | 6y+-18=8y | | y=3x+9 | | 11a-8b=4a=8b=44 | | X^2-4x+15=7-13x | | y=3x^2-8 | | 3(2X+3)-2(3X+2)=-3(X+2)+2 | | 4x^3+4x^2+x=0.00002 | | 42-3x=60 | | 2u+5=1 | | 16-(3-9b)=8+7b+5 | | -2p^2+6p+3=0 | | -p^2+6p+3=0 | | (3x-2)(5x+4)=0 | | 272-37x=-45x | | 9x+3=4x+9 | | x^2-10x=37 | | (2x^2+3x-6)+(x^2-18x+6)= | | 4x-6=-14 | | 2x^4+16x^2=4 | | 3x-8=20x+26 | | x^2+14x=-10 | | 2((42-3x)+x)=60 |